KEMAMPUAN PROFITABILITAS MEMODERASI PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Merta Sari, Ni Luh Kade; Dwija Putri, I.G.A.Made Asri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.10.TAHUN 2016, 2016)
The present study is aimed at providing empirical evidence on the impact of profitability on the correlation among liquidity and leverage of financial distress. The population included in this study was manufacturer listed in Indonesian stock exchange from 2009 to 2013 period with total sample of 565 companies. The sample collection method used was purposive sampling and the testing measurement used was logistic regression analysis. The result of this study proves that liquidity affect negative to financial distress, leverage affect positively to financial distress, profitability does not affect financial distress, profitability able to moderate the affect of liquidity to financial distress, profitability able to moderate the affect of leverage to financial distress.
Keywords: liquidity, leverage, profitability, financial distress